Effects of polysaccharide fermentation with Bacillus coagulans on growth, antioxidant and immunity of Macrobrachium nipponense (riental river prawn) - Yachao Wang; Yilei Liang; Jing Yu; Zhengzhong Li; Wei Wang; Li Jiang; Bo Liu (Frontiers in Marine Science, 2024)
Introduction In recent years, with the continuous expansion of aquaculture areas worldwide and the outbreak of diseases, the use of antibiotics and chemical drugs is limited. Plant polysaccharides have received widespread attention due to their multiple bioactivities. However, research on the combined use of plant polysaccharides and Bacillus coagulans is still insufficient. Therefore, this study focuses on the impact of B.coagulans -fermented polysaccharides on Macrobrachium nipponense . Methods An 8-week feeding trial was conducted with seven groups: the control group (CT) and the Bacillus coagulans group (N), Atractylodes macrocephala polysaccharides group (NB), Saposhnikovia divaricata polysaccharides group (NF), Mannose group (NG), Astragalus polysaccharides group (NH) and Yu ping feng polysaccharides group (NP). Results and discussion The research results indicate that compared to the CT, the levels of AST and ALT were reduced in the group of N, NF and NG. The NF showed a significant increase in total antioxidant capacity (T-AOC) and total superoxide dismutase (SASC) levels. The NP had a significant increase in T-AOC and superoxide anion scavenging ability. The levels of total protein (TP) and malondialdehyde (MDA) in the group of NG, NB, and NP were significantly higher than those in the CT and N. Compared to the CT, the expression of Toll in the NP group, Myd88 and Dorsal in the NH group, and IMD and Relish in the NF and NP group were all significantly increased. Conversely, the expression of IMD in the NB and NG group and Relish in the NG group was significantly decreased. Additionally, the survival rate in the NP group was significantly higher than in other groups, and the NB group enhanced the weight gain of M.nipponense compared to the N. In summary, B.coagulans fermented with Yupingfeng polysaccharides and Astragalus polysaccharides can significantly enhance the antioxidant and immune capabilities of M.nipponense.